Cortisol Levels in Chronic Primary Dysmenorrhoea Patients and Non-Dysmenorrhoea : A Cross- Sectional Study: Kadar Kortisol antara Pasien Dismenorea Primer Kronis: Sebuah Studi Potong Lintang - Yodi Ertandri; Syahredi S. Adnani; Hafni Bachtiar (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To investigate whether chronic primary dysmenorrhoea will significantly increase cortisol levels in the body. This study can provide an overview of the importance of handling primary dysmenorrhoea so that it does not continue to become menstrual disorders.Method: This study used a cross-sectional comparative study method with a total sample of 26 subjects with 13 subjects included in the dysmenorrhea group and 13 other subjects belonging to the non-dysmenorrhea group. The study was conducted at Department of Obstetrics and Gynecology Faculty of Medicine Universitas Andalas network primary healthcare and Dr. M. Djamil Padang Central General Hospital. Data were analyzed using computational calculation of SPSS program with bivariate test using X2 test or chi-square test with a significance degree of 0.05.Results: Twenty six subjects (13 each group) have been sampled in this study, the mean age of the dysmenorrhea group was 26.23 ± 3.92 while the mean age of the non-dysmenorrhea group was 28.62 ± 7.10. The age difference between groups was not statistically significant with a value of p = 0.30 (p> 0.05). In the comparison of cortisol levels between the two groups, it was found that the dysmenorrhea group had a higher cortisol level of 72.3077 (7.2 µg / dL) compared to the non-dysmenorrhoea group of 60.3846 (6 µg / dL). Based on the results of the bivariate analysis using the chi-square test, the value of p = 0.148 (P> 0.05) showed that there was no significant difference between the cortisol levels of the group with chronic primary dysmenorrhea compared with the non-dysmenorrhea group.Conclusion: Chronic primary dysmenorrhea can not significantly increase cortisol levels in the body.Keywords: comparative study, chronic primary dysmenorrhea, cortisol levels, non-dysmenorrhea, menstrual disorders Abstrak Tujuan :Mengetahui apakah dismenorea primer kronis akan meningkatkan kadar kortisol dalam tubuh secara signifikan. Penelitian ini dapat memberikan gambaran pentingnya penanganan dismenorea primer agar tidak berlanjut menjadi gangguan menstruasi.Metode :Penelitian ini merupakan penelitian dengan desain potong lintang studi banding dengan jumlah total sampel sebanyak 26 subjek dengan rincian 13 subjek termasuk ke dalam kelompok dismenore dan 13 subjek lainnya termasuk ke dalam kelompok non-dismenore. Penelitian dilakukan di Puskesmas jejaring PPDS Obgyn FK Unand dan RSUP Dr. M. Djamil Padang. Data dianalisis menggunakan perhitungan komputasi program SPSS dengan uji bivariat menggunakan ujiX2 atau uji chi-square dengan derajat kemaknaan 0,05. Hasil : Dari 26 subjek (masing-masing 13 subjek) yang dijadikan sampel dalam penelitian ini, didapatkan usia rerata kelompok dismenore ialah 26,23 ± 3,92 sedangkan usia rerata kelompok non-dismenore ialah 28,62 ± 7,10. Perbedaan rerata usia antar kelompok ini tidak signifikan secara statistik dengan nilai p = 0,30 (p > 0,05). Pada perbandingan kadar kortisol antar kedua kelompok, didapatkan kelompok dismenore memiliki kadar kortisol yang lebih tinggi yaitu 72,3077 (7.2 µg/dL) dibandingkan dengan kelompok non-dismenorea yaitu 60,3846 (6 µg/dL). Berdasarkan hasil analisis bivariat menggunakan uji chi-square, didapatkan nilai p = 0,148 (P > 0,05) yang menunjukkan tidak adanya perbedaan yang signifikan antara kadar kortisol kelompok dengan dismenore primer kronis dibandingkan dengan kelompok non-dismenore.Kesimpulan : Dismenore primer kronis dapat meningkatkan kadar kortisol dalam tubuh secara signifikan.Kata kunci : dismenore primer, gangguan menstruasi, kadar kortisol, kronis, tidak dismenore, studi perbandingan